HUBUNGAN MINAT BELAJAR SISWA DENGAN HASIL BELAJAR DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Yusril, Elvina; Alwi, Elma; Taufik, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
AbstractThe research aim to know there is or no correlation between studen’s interest in learning and learning outcomes in social sciences learning of fifth grade of primary school on cluster four in Bauhampu. The type of research is correlation. The amount of sample is 61 students, fifth grade of primary school on cluster four in Banuhampu. The